Chronic exposure to dim artificial light at night decreases fecundity and adult survival in Drosophila melanogaster. (July 2017) - McLay, L.K.; Green, M.P.; Jones, T.M
Graphical abstract: Highlights: Effect of dim night lighting intensities on growth, reproduction and survival in D. melanogaster . Oviposition initiation and egg number was suppressed at night-light intensities ≥ 1 lux. Adult survival was reduced at lighting intensities above 1 lux. Further investigation into the mechanisms causing these biological outcomes is warranted. Abstract: The presence of artificial light at night is expanding in geographical range and increasing in intensity to such an extent that species living in urban environments may never experience natural darkness. The negative ecological consequences of artificial night lighting have been identified in several key life history traits across multiple taxa (albeit with a strong vertebrate focus); comparable data for invertebrates is lacking. In this study, we explored the effect of chronic exposure to different night-time lighting intensities on growth, reproduction and survival in Drosophila melanogaster . We reared three generations of flies under identical daytime light conditions (2600 lx) and one of four ecologically relevant ALAN treatments (0, 1, 10 or 100 lx), then explored variation in oviposition, number of eggs produced, juvenile growth and survival and adult survival. We found that, in the presence of light at night (1, 10 and 100 lx treatments), the probability of a female commencing oviposition and the number of eggs laid was significantly reduced. This did not translate into differences at the juvenile phase: juvenile development times and the probability of eclosing as an adult were comparable across all treatments. However, we demonstrate for the first time a direct link between chronic exposure to light at night (greater than 1 lx) and adult survival. Our data highlight that ALAN has the capacity to cause dramatic shifts in multiple life history traits at both the individual and population level. Such shifts are likely to be species-specific, however a more in depth understanding of the broad-scale impact of ALAN and the relevant mechanisms driving biological change is urgently required as we move into an increasing brightly lit future.